Effects of limb dominance on the symmetrical distribution of plantar loading during walking and running - Gao, Z.; Mei, Q.; Xiang, L.; Baker, J. S.; Fernandez, J.; Gu, Y. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2022)
The purpose of this study was to investigate the symmetry or asymmetry in the plantar pressure, foot axis angle and muscle mass of dominant and non-dominant legs. Sixty-eight able-bodied participants (age: 20 ± 1 years, height: 162 ± 8 cm, mass: 53 ± 7 kg, BMI: 20.63 ± 2 kg/m2) were recruited for the walking and running tests. All participants with right dominant feet, defined as the preferred leg when kicking a ball, were asked to perform four successful trials at their self-selected walking and running speeds after warm-up. FootScan force-measuring plate was utilized to collect plantar pressure and foot axis angle. The Tanita Segmental Body Composition Analyzer was used to measure the muscle mass of the lower limbs. The time-series parameters were checked using an open-source statistical parametric mapping 1d package. The result exhibited that the medial foot pressure of the dominant limb was higher than the non-dominant limb (p < 0.05). Foot balance index range showed asymmetry in both walking and running tasks (absolute symmetry index <10%). There was no significant difference in muscle mass between the dominant and non-dominant lower limbs (p = 0.79). The quantification of potential differences and asymmetries could provide implications for gait injury prevention and shoe design.